2009
DOI: 10.1124/jpet.109.159178
|View full text |Cite
|
Sign up to set email alerts
|

Sulfhydryl Angiotensin-Converting Enzyme Inhibitor Promotes Endothelial Cell Survival through Nitric-Oxide Synthase, Fibroblast Growth Factor-2, and Telomerase Cross-Talk

Abstract: The protective effect exerted by angiotensin-converting enzyme inhibitors (ACEI) in cardiovascular diseases caused by endothelial injury and aging has been attributed to the restoration of endothelial cell functions. Recently, we demonstrated a central role of the fibroblast growth factor-2 (FGF-2)/FGF receptor-1 system in mediating the acquisition of an angiogenic phenotype in coronary microvascular endothelium exposed to ACEI. Here, we report on the rescuing effect of ACEI on impaired endothelium and the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 40 publications
4
32
0
1
Order By: Relevance
“…Apart from autophagy and apoptosis, mitochondrial-ROS contributes to RAS-induced cell senescence. ROS-induced protein S-nitrosylation seems to be the major contributor, while sulfhydryl-ACEI promotes endothelial cell survival and delays senescence [15,30]. The present study provides evidence that high-glucose- or Ang-induced mitochondrial ROS increase causes increases in SA-β-gal- or SAHF-positive cell numbers, cell cycle arrest and p21 protein expression.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Apart from autophagy and apoptosis, mitochondrial-ROS contributes to RAS-induced cell senescence. ROS-induced protein S-nitrosylation seems to be the major contributor, while sulfhydryl-ACEI promotes endothelial cell survival and delays senescence [15,30]. The present study provides evidence that high-glucose- or Ang-induced mitochondrial ROS increase causes increases in SA-β-gal- or SAHF-positive cell numbers, cell cycle arrest and p21 protein expression.…”
Section: Discussionsupporting
confidence: 52%
“…Disrupting RAS has been shown to provide significant benefit for cellular function, and this effect has been shown to be reliant on mitochondrial-ROS [12,13,14,15]. Angiotensin II (Ang) exposure or overexpression of Ang type 1 receptor (AGTR1)-coupled-G-protein, Gaq, induces excessive ROS production and triggers autophagy, senescence and apoptosis in cardiomyocytes and smooth muscle cells [8,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…pERK1/2 and p53 were evaluated by western blot in EC treated with 0.5 μM doxorubicin (D) for 1 h, while the cleavage of caspase-3 was monitored by western blotting in EC exposed to doxorubicin for 6 h. P53 mediated-apoptosis and impairment of survival were reverted by treatment with zofenoprilat (Z), added at 1-100 μM concentration together with doxorubicin. The previously described prosurvival signaling pathway (activation of PI-3K dependent eNOS and upregulation of endogenous FGF-2 and telomease reverse transcriptase TERT) [77] was not involved in the protective effect of doxorubicin induced damage, which, instead, could be ascribed to cystathionine gamma lyase (CSE) dependent availability of H 2 S from zofenoprilat. Indeed the levels of CSE protein were upregulated by zofenoprilat treatment (10 μM, 4 h) [78] ( Fig.…”
Section: Nitric Oxide Donorsmentioning
confidence: 81%
“…We have recently reported that ACEi dependent H 2 S exerts protective activity on ECs through activation of K ATP channel, PI-3 K and eNOS, as well as up-regulation of FGF-2 and telomerase, thus maintaining endothelial longevity and function [76][77][78]104] (Fig. 4).…”
Section: Nitric Oxide Donorsmentioning
confidence: 99%
See 1 more Smart Citation